Gambaran Tingkat Pengetahuan Ibu Balita tentang Pencegahan Covid pada Balita : Mother of Toddlers Level of Knowledge Concerning Prevention of Covid in Toddlers - Puspa Kusumaningsih, Tri; Fetty Chandra Wulandari; Rahajeng Anindita (Universitas Ngudi waluyo, 2024)
Covid-19 is caused by a corna virus called Sars-Cov 2. Children's growth and development monitoring, immunization services, and Covid-19 case prevention and treatment services are priority activities. According to the results of interviews with 9 mothers with young children, 5 mothers with young children do not know how to prevent Covid in toddlers and 4 mothers with young children know how to prevent Corona virus in toddlers. The aim of this study was to determine the level of knowledge of mothers of young children about Covid prevention in toddlers in Kedunggubah village, Kaligesing district. Method : This study used a descriptive method with a cross sectional design. The population in this study was mothers who had children aged <5 years in Kedung Gubah Village, Kaligesing District, Purworejo Regency and used a total sampling of 41 people. Using Univariate data analysis, validity test using pearson product moment and reliability test using KR 20 and data program using SPPS Results sample of 41 people, total sampling method, data collection technique by questionnaire, univariate analysis, validity test by Pearson product moment and reliability test by KR 20 and program Process data using SPPS 16.0 Result : Research results show that there are 29 respondents with a good level of knowledge (70.7%), 6 respondents with a moderate level of knowledge (14.6%) and 6 respondents with a high level of knowledge. low knowledge (14.6%). ). Conclusion : Most of those surveyed are aware of the Corona virus prevention in toddlers. Governments and health workers should continue to promote their health, as part of prevention. Abstrak Covid-19 disebabkan oleh virus corna yang dinamakan Sars-Cov 2. Aktivitas pemantauan tumbuh kembang bayi , pelayanan imunisasi dan pelayanan pencegahan maupun penanganan kasus Covid-19 menjadi kegiatan prioritas. Dari hasil wawancara dengan 9 ibu balita, ada 5 ibu balita yang belum mengetahui tentang pencegahan Covid pada balita, dan ada 4 ibu balita yang sudah mengetahui pencegahan corona virus pada balita. Tujuan Penelitian ini untuk mengetahui tingkat pengetahuan ibu balita tentang pencegahan Covid pada balita di Desa Kedunggubah Kecamatan Kaligesing. Metode : Penelitian ini menggunakan metode deskriptif dengan rancangan cross sectional. Populasi dalam penelitian ini ibu yang memiliki anak usia <5 tahun di Desa Kedung Gubah, Kecamatan Kaligesing, Kabupaten Purworejo dan menggunakan total sampling sebanyak 41 orang. Menggunakan analisa data Univariat, uji validitas menggunakan pearson product moment dan uji reabilitas menggunakan KR 20 dan program data menggunakan SPPS Hasil : Hasil penelitian menunjukan bahwa responden dengan tingkat pengetahuan baik sebanyak 29 orang (70,7%), responden dengan tingkat pengetahuan cukup sebanyak 6 orang (14,6%), dan responden dengan tingkat pengetahuan kurang sebanyak 6 orang (14,6%). Kesimpulan : Sebagian besar responden telah mengetahui pencegahan corona pada balita, pemerintah dan tenaga kesehatan diharapkan terus meningkatkan promosi kesehatannya, sebagai bagian dari pencegahan.